2003
DOI: 10.1523/jneurosci.23-01-00230.2003
|View full text |Cite
|
Sign up to set email alerts
|

Normal Female Sexual Development Requires Neuregulin–erbB Receptor Signaling in Hypothalamic Astrocytes

Abstract: The initiation of mammalian puberty requires the activation of hypothalamic neurons secreting the neuropeptide luteinizing hormone-releasing hormone (LHRH). It is thought that this activation is caused by changes in trans-synaptic input to LHRH neurons. More recently, it has been postulated that the pubertal increase in LHRH secretion in female animals also requires neuron-glia signaling mediated by growth factors of the epidermal growth factor (EGF) family and their astrocytic erbB receptors. Although it appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
188
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(198 citation statements)
references
References 40 publications
9
188
0
1
Order By: Relevance
“…ErbB4 receptors have either not been detected (Prevot et al, 2003) or TGFa is a gliatrophin for astrocytes A Sharif et al were observed at low levels (Elenius et al, 1997;Francis et al, 1999) in astrocytes cultures derived from newborn rat cortices. ErbB3 expression has been found in one study (Francis et al, 1999) and not in another (Pinkas-Kramarski et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ErbB4 receptors have either not been detected (Prevot et al, 2003) or TGFa is a gliatrophin for astrocytes A Sharif et al were observed at low levels (Elenius et al, 1997;Francis et al, 1999) in astrocytes cultures derived from newborn rat cortices. ErbB3 expression has been found in one study (Francis et al, 1999) and not in another (Pinkas-Kramarski et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that the secretory activity of GnRH neurons is controlled by both neuronal and glial input (12,13,15,16). Whereas glutamate is a key neurotransmitter involved in the transsynaptic activation of GnRH neurons (17, 18), prostaglandin E 2 (PGE 2 ) mediates cell-cell communication between astrocytes and GnRH neurons (6,19,20). A functional connection between the two systems is demonstrated by the ability of glutamate to elicit PGE 2 release from astrocytes (21-23).…”
mentioning
confidence: 99%
“…I t is increasingly clear that astrocytes play an important role in maintaining central nervous system function (1-3) and controlling key bodily processes, such as breathing (4), sleep (5), and reproduction (6). Because of their perivascular and interneuronal localization, astrocytes are well positioned to sense afferent neuronal and blood-borne signals and ideally suited for the temporal and spatial propagation of these signals (7)(8)(9).…”
mentioning
confidence: 99%
“…DNerbB4 is a truncated receptor lacking the tyrosine kinase domain and phosphorylation sites (20). DN-erbB4 expression completely blocks erbB2, erbB3, and erbB4 receptor signaling (18,20,21) without affecting signaling by other receptors, e.g., the EGF receptor, an erbB family member (21). Two Tg lines that express high levels of DN-erbB4, CNP3 and CNP48, were characterized and exhibited similar phenotypes.…”
mentioning
confidence: 99%